Adapting to Higher Energy Costs : Public Perspectives and Responses to Rising Energy Costs in Europe and Central Asia - World Bank (Washington, DC, 2015)
This report presents findings from 208 focus group discussions held across 8 countries in Eastern Europe and Central Asia between 2013-2014 that examined households experiences with and attitudes to energy tariff reforms. Over the past five years, the World Bank has provided guidance to more than 14 countries in the region on implementing energy subsidy reforms. This work complements a large body of research on the poverty impacts of these reforms. Specifically, it gives voice to poor and middle-income citizens, and presents their perspectives and concerns with regard to rising tariffs and reforms in the energy sector overall. The report argues that by gaining a deeper understanding of the narratives that people attach to energy issues, governments can design better mitigation policies to address the reforms adverse impacts; better communication campaigns to convey the rationale of reforms to the public; and institute stronger accountability measures to help citizens protect their rights as consumers. This report examines poverty and social impacts of energy tariff reforms in the ECA region from citizens perspectives. It aims to complement previously collected quantitative data on distributional impacts of reforms, and contribute to the design of socially sustainable energy policies and effective mitigation measures. It presents qualitative research findings that highlight: (i) factors affecting household vulnerability to energy tariff increases; (ii) insights into how households cope with increasing energy prices; (iii) experiences with and perceptions of energy sector institutions and, more specifically, interactions with energy service providers; (iv) experiences with social assistance programs and overall attitudes toward measures that make energy more affordable; and (v) consumer attitudes toward energy sector reforms overall.